Plan de marketing para la empresa de servicios médicos y de salud “Clínica sudamericana”, de la ciudad de Quevedo, año 2015 - González Luna, Darío Xavier (2016)
This research was conducted in the canton Quevedo, Los Rios Province, Republic of Ecuador, during the year 2015 left the problem: marketing plan for the company's Medical Services "American Health Clinic? Its overall objective "Designing a marketing plan for the company Medical and Health Services" American Clinic ". The analysis of the current problems of the clinic allowed to formulate the problem, raise the objectives and perform due justification, the conceptual and referential framework was developed on the basis of relevant theories and concepts related to the objectives, methods are identified, types and techniques, determination of the population and the respective sample that was used to apply an interview with the owner of the clinic manager allowed to know the strengths, weaknesses, opportunities and threats of the company; by applying the survey to citizenship it was determined that 100% of respondents believe it is very important to implement new services to improve the quality of services. He reached the following conclusions: Market research on the positioning of the clinic " American " showed that it has a low position and is located in the last places in remembrance of the market; The strategies of the marketing plan for the clinic " American " 2015 , are: the product strategy, the new brand slogan is " Providing better service " pricing strategy is to reduce the values that are below competition. The promotion strategy used an advertising campaign which will be handled by the media ATL ( billboards , leaflets, LED screen ), direct marketing, sales promotions : calendars, win a bike ; The budget plan means reaches a value of $ 9,000.00 which will be used to create a marketing plan.